Strategy for Enhancing Critical Reasoning Skills through the Jigsaw Model in Civics Education Learning - Bundel, Bundel (Institut of Shanti Bhuana, 2025)
Critical thinking skills are essential competencies that must be developed in education, particularly in Civic Education (PPKN) learning. However, in practice, conventional teacher-centered teaching methods still dominate elementary schools, providing limited opportunities for students to think critically and analytically. This study aims to analyze the effectiveness of the Jigsaw cooperative learning model in enhancing students' critical thinking skills in PPKN subjects. The research employs a quasi-experimental method with a Nonequivalent Control Group Design, involving two groups: an experimental group using the Jigsaw learning model and a control group applying conventional methods. The sample was selected through purposive sampling, consisting of 86 fourth-grade elementary school students divided into two groups. Data were collected using pretests and posttests to measure students' critical thinking abilities before and after the intervention. The results showed a significant difference between the experimental and control groups, with the experimental group achieving higher posttest scores and greater improvement. The Jigsaw model boosted student engagement, independent analysis, and confidence in expressing opinions. Its success was supported by clear group roles, a conducive environment, and teacher guidance, though challenges included varying comprehension levels, time limits, and communication issues. Overall, the Jigsaw model proved more effective than traditional methods in enhancing critical thinking, making it a valuable approach for PPKN learning. The study suggests the need for teacher training and supportive school environments.